Political Parties And The Direction of Political Development in The Republic of Tatarstan - Vladimirov Mladenov, Stanislav; Abdul Muqsith, Munadhil; Setiawan, Refly (JASSP, 2021)
Political parties reflect a democratic state, which is believed to be a condition for modern state life. As institutions for channeling interests, political parties are used as communication with a two-way function, namely, top-down and bottom-up. If this can be carried out well, then political parties' function as political socialization, political participation, political communication, articulation of interests, aggregation of interests, and policymaking can run well to realize the expected political development. The research method used in this research is qualitative research methods. Through qualitative research, the author has created a complex picture, examined words, reviewed detailed reports from the point of view of resource persons, and conducted studies on natural situations. This study aims to determine direction of political parties' development in the Russian Republic of Tatarstan, political parties' function, and political development amid a society in this modern era. The problem in this research is that political parties in Russia tend to have their own interests, either from the central government or the state or Federation governments. In addition, there tends to be a mismatch between the central and state governments in decision making. In fact, in the context political parties can be a tool for realizing development in a country. Even though there are problems, the results showed that political parties in the Republic of Tatarstan rated quite well in carrying out their functions by the functions of political parties according to the Law of the Russian Federation and the Law of the Republic of Tatarstan concerning Political Parties. The development of political parties in the Tatarstan Republic has played a role in controlling conflicts of interest among the Republic of Tatarstan.